The Study of Misconceptions in the 12th Grade Biology Textbooks: Focus on the Linkage and Crossing Over topics - Alexandra Jeni Yoesianata; Wolly Candramila Candramila; Eko Sri Wahyuni (IJIS Edu : Indonesian Journal of Integrated Science Education, 2025)
Misconceptions in textbooks can hinder students' understanding, especially in abstract and molecular topics like linkage and crossing over. This study aims to identify and analyze misconceptions in the linkage and crossing over subtopics in four biology textbooks for 12th grade. The content analysis method used includes the steps of unitizing, sampling, recording/coding, reducing, inferring, and narrating. Data are analyzed using the tabulation method to categorize findings and concepts according to reference materials, along with peer debriefing to ensure data validity by involving experts. Of the 11 key concepts analyzed, none of the four textbooks present them completely. The most common misconception is oversimplification (18 out of 34 items). The highest number of misconceptions was found in Book D (12 items), while Book B had the fewest (6 items). Learning barriers caused by misconceptions require an increased role for teachers in identifying and correcting conceptual errors in textbooks, as well as enriching lessons with more accurate scientific sources.